2011
DOI: 10.1371/journal.pone.0019226
|View full text |Cite
|
Sign up to set email alerts
|

Findings from a Rapid Assessment of Avoidable Blindness (RAAB) in Southern Malawi

Abstract: BackgroundData on prevalence and causes of avoidable blindness in Malawi are not readily available. The purpose of this study was to determine the prevalence and causes of blindness in persons aged 50 and above in southern Malawi to plan eye care services for the community.MethodologyA population-based survey was conducted in 7 districts in southern Malawi. Villages were selected by probability proportionate to size within each district. Clusters were further subdivided into segments. A predetermined number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
47
5

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 14 publications
8
47
5
Order By: Relevance
“…The proportion of good outcomes (and corresponding low percentage of poor outcomes) in clinic-based studies is higher than in population-based surveys in sub-Saharan Africa [14][15][16][17]. However, findings from clinic-based studies such as ours may not be representative of the wider population.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…The proportion of good outcomes (and corresponding low percentage of poor outcomes) in clinic-based studies is higher than in population-based surveys in sub-Saharan Africa [14][15][16][17]. However, findings from clinic-based studies such as ours may not be representative of the wider population.…”
Section: Discussioncontrasting
confidence: 61%
“…However, findings from clinic-based studies such as ours may not be representative of the wider population. A recent rapid assessment survey of avoidable blindness in southern Malawi revealed that 52.6 % of operated eyes had a good outcome (could see 6/18) with pinhole-correction, and, encouragingly, the majority of cataract operations (91.0 %) used IOLs [17]. Although there was a high proportion (32.1 %) that could not see 6/60 with best correction, most subjects were very or partially satisfied with the visual outcome (84.8 % of all persons who had surgery) with only 3 % very unsatisfied.…”
Section: Discussionmentioning
confidence: 99%
“…The only other country contributing two separate published studies was Tanzania, including RAAB surveys from Kilimanjaro and Zanzibar 20 21. Additional RAAB surveys were performed in Botswana,9 Burundi,22 Malawi,17 Rwanda,19 Eritrea12 and Kenya 16. Five studies were national surveys 9 12–14 18.…”
Section: Resultsmentioning
confidence: 99%
“…5,6,[8][9][10]14,15 In contrast, Powe and colleagues found that 89.7% of all eyes with cataract operated in the United States mostly during the 1980s-when conventional extracapsular surgery predominated-achieved visual acuity of 20/40 or better. 16 While developing country cases with advanced cataracts and possibly neglected co-morbidities likely are fundamentally more difficult and less likely to lead to good outcomes than US cases were in the 1980s, and the method of ascertaining visual outcome is non-identical, there appears to be a large quality gap.…”
Section: John H Kempenmentioning
confidence: 97%
“…At the most straightforward level, the results show us that blindness remains a major problem in Eritrea, and that diseases such as cataract and glaucoma which require ophthalmic care are an important cause of blindness, as in several other surveys from Africa and elsewhere in the world. [5][6][7][8][9][10][11][12][13][14][15] While more than half of severe visual loss or blindness was attributed to cataract, only about 1% was attributed to surgical complications. However, in reading further (as noted by the authors), we find that blindness due to complications of cataract surgery must be one of the leading causes of blindness in single eyes, because 182 eyes (39.2% of those operated) present with visual acuity worse than 6/60.…”
Section: John H Kempenmentioning
confidence: 99%